How Does the Presence of Diabetes Affect the Course of Acute Coronary Syndrome in Elderly Patients in Actual Clinical Practice? - M. R. Atabegashvili; E. V. Konstantinova; M. D. Muksinova; A. E. Udovichenko; A. P. Nesterov; M. O. Zheltoukhova; L. S. kyzy Muradova; M. Y. Gilarov (Рациональная фармакотерапия в кардиологии)
The number of elderly patients with diabetes mellitus (DM) is constantly growing in general population. Accordantly, we have the growth of such patients in the group of acute coronary syndrome (ACS).Aim. To compare clinical characteristics of the elderly patient (>75 years old) with and without DM.Material and methods. This retrospective study included 1133 ACS patients who were aged ≥75 years and admitted to the City Clinical Hospital №1 from 01.01.2015 to 31.12.2016. Median age was 80 years, 66% were women. We analyzed 4 patient subgroups: Group 1 – 105 patients with ST-segment elevation myocardial infarction (STEMI) and DM, Group 2 – 254 STEMI patients without DM, Group 3 – 222 non-STEMI patients with DM and Group 4 – 552 non-STEMI patients without DM. We used Student’s t-test and c2 tests to find significant difference between pairs of groups.Results. Median age of patients in 4 groups was 80, 81, 81 and 80 years (p>0.05), age variance was 75-100 years. DM was found in 29% of all elderly patients with no difference between STEMI and non-STEMI groups. STEMI and non-STEMI patients with DM were more likely women. NonSTEMI patients with DM more often had hypertension, previous stroke, lower median Hb (121 vs 127 g/l; p<0.001). Angiography data demonstrated more often three-vessel disease (43% vs 29.7%) and less one-vessel disease (15% vs 25.6%; p<0.05) between groups 3 and 4. Glomerular filtration rate (GFR) <60 ml/min/1.73 m2 occurred in 74%, 73%, 77% and 74% in patients of 4 groups (p>0,05), but GFR<45 ml/min/1.73 m2 was more prevalent in patients with DM than without DM: 45%, 39%, 45%, 36% in 4 groups. Finally, mortality rates didn’t demonstrate significant difference between DM and non-DM patients with STEMI (10% vs 13%; p>0.05) and non-STEMI (7% vs 7%) groups.Conclusion. DM is associated with ACS approximately in one third of the elderly patients and is not associated with its type (STEMI or non-STEMI). In STEMI and non-STEMI patients the female sex and GFR level <45 ml/min/1.73 m2 were associated with DM. In non-STEMI group multi-vessel disease and presence of hypertension and previous stroke were associated with DM. We didn’t find any difference between mortality in elderly patients with and without DM.